PENGARUH KETIDAKPASTIAN DUNIA, KETIDAKPASTIAN KEBIJAKAN EKONOMI, RASIO KECUKUPAN MODAL, KREDIT BERMASALAH TERHADAP PROFITABILITAS BANK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Foe, Liota; Tulung, Joy; Rumokoy, Lawren (FEB Universitas Sam Ratulangi Manado, 2024)
Abstract: This study examines the influence of external and internal factors on the profitability of banks listed on the Indonesia Stock Exchange (IDX) between 2019 and 2023. Specifically, it investigates the impact of world uncertainty and economic policy uncertainty (external factors), as well as the Capital Adequacy Ratio (CAR) and Non-Performing Loans (NPL) (internal factors). Using secondary data sourced from the annual reports of these banks, a panel data regression analysis was conducted, employing the random effects model to assess these relationships. The results indicate that world uncertainty and CAR positively influence bank profitability, while NPL has a negative effect. In contrast, economic policy uncertainty is found to have an insignificant impact on profitability. This research contributes to understanding how both global and internal dynamics shape the financial performance of banks in Indonesia, providing insights for policymakers and financial institutions aiming to navigate uncertainties. Keywords: Bank Profitability, World Uncertainty, Economic Policy Uncertainty, Capital Adequacy Ratio, Non-performing Loans